2017
DOI: 10.2337/db16-0993
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Activation of the FAM3C-HSF1-CaM Pathway Attenuates Hyperglycemia of Obese Diabetic Mice

Abstract: FAM3C is a member of the family with sequence similarity 3 (FAM3) gene family, and this study determined its role and mechanism in regulation of hepatic glucose/lipid metabolism. In obese diabetic mice, FAM3C expression was reduced in the liver, and hepatic FAM3C restoration improved insulin resistance, hyperglycemia, and fatty liver. FAM3C overexpression increased the expression of heat shock factor 1 (HSF1), calmodulin (CaM), and phosphorylated protein kinase B (Akt) and reduced that of gluconeogenic and lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 50 publications
3
56
0
Order By: Relevance
“…However, whether they are coordinated to promote the development of cancers remains unknown. 44 The current and our previous findings 27,28 revealed that FAM3C likely mediates TGFβ-promoted Akt activation in the pathogenesis of EMT through YY1-HSF1 signalling axis. FAM3C up-regulates YY1 to induce HSF1 expression, finally activating Akt-Cyclin D1 pathway to promote the proliferation and migration of breast cancer cells.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…However, whether they are coordinated to promote the development of cancers remains unknown. 44 The current and our previous findings 27,28 revealed that FAM3C likely mediates TGFβ-promoted Akt activation in the pathogenesis of EMT through YY1-HSF1 signalling axis. FAM3C up-regulates YY1 to induce HSF1 expression, finally activating Akt-Cyclin D1 pathway to promote the proliferation and migration of breast cancer cells.…”
Section: Discussionmentioning
confidence: 66%
“…27,28 However, in case of TGFβ overproduction, long-term activation of FAM3C-YY1-HSF1 pathway will trigger the development of cancers in various tissues including breast tissue by promoting excessive Akt activation. Under insulin resistance, repression of FAM3C by the factors such as fatty acids will impair YY1-HSF1-Akt pathway to enhance hepatic gluconeogenesis and lipogenesis, exaggerating hyperglycaemia and fatty liver.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations